Comparison of Mercury Intrusion and Nitrogen Adsorption Measurements for the Characterization of Certain Natural Raw Materials Deposits (Baghdad Science Journal, 2025)
The porosity of materials is important in many applications, products and processes, such as electrochemical devices (electrodes, separator, active components in batteries), porous thin film, ceramics, soils, construction materials, ..etc. This can be characterized in many different methods, and the most important methods for industrial purposes are the N2 gas adsorption and mercury porosimetry. In the present paper, both of these techniques have been used to characterize some of Iraqi natural raw materials deposits. These are Glass Sand, Standard Sand, Flint Clay and Bentonite. Data from both analyses on the different types of natural raw materials deposits are critically examined and discussed. The results of specific surface areas showed considerable difference between the two sets of data on the same material. This indicates that the material have an external surface which can not be measure by mercury porosimeter. Also pore size distribution data obtained from N2 adsorption measurements shows a wide range of the smallest pore size. This result suggests that materials have micropores using IUPAC definitions of pore size.